EMPOWERING MUZAKKI THROUGH DIGITAL MEDIA PLATFORMS IN COLLECTING ZAKAT FUNDS IN BAZNAS - Fharadilla, Niken; Muhtadi, Muhtadi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2023)
The digital era that is currently happening in Indonesia has an impact on changes in people's patterns of behavior, causing many activities to be carried out digitally. This condition also occurs in online zakat activities through digital media platforms. With the development of digital fundraising, simultaneously it also encourages Muzakki; a person who pays zakat, to utilize digital technology to adapt so that they can fulfill their zakat obligations effectively and efficiently. This study aims to determine digital communication management on digital media platforms so that it can increase the number of zakat funds at Banten Province BAZNAS and find out strategies for empowering Muzakki through digital media platforms so that Muzakki can fulfill their zakat obligations online through the digital media platform owned by Banten Province BAZNAS. This research is presented using a descriptive qualitative research method in the form of a case study. Data sources from primary data and secondary data with data collection techniques of interviews, observation, and documentation. The data analysis techniques used in this study were data reduction, data presentation, drawing conclusions, verifying findings, and validating the validity of the data. The results of this study explain that there is digital communication management in utilizing the Banten Province BAZNAS digital media platform for collecting zakat funds. In addition, the empowerment of Muzakki is carried out with three stages, namely the awareness stage and the formation of conscious behavior, the knowledge transformation stage, and the intellectual ability improvement stage so that Muzakki becomes empowered and independent to become regular Muzakki on the Banten Province BAZNAS digital media platform.